Identidades de gênero no espaço escolar: silêncios e falas - Castro, Nathalie Nunes Daltro de (2016)
Gender identities occupy all the spaces, and in particular the school space. There are disciplinarizadas, silenced through various silencing mechanisms, for example, curriculum policies, the daily actions between teachers, staff and students, the imposition of heteronormative behavior in the hidden curriculum, processes that occur from the remotest childhood to the end of the school career and are not restricted to the school environment, but help to make models of society. However, the bodies are not docile, although moldable, subject to the order, also produce lines, seek subversion spaces (mis) direction. So, I question this work as schools in (ex) clude gender identities at school and how the subjects that compose it (un) build models and standards. I sought to answer this question by immersion in school dynamics from areas beyond the school building, but also in it, mainly the virtual environment. Understanding that the Internet has great potential with the juvenile used a dynamic application for mobile phones and social networking, Whatsapp and Facebook, as a guide to promote debates on gender identities. In this work, articulate Foucault's studies, post-critical studies and queer studies that have been tailored to the field research, data these that were collected through the dialogues in the mobile application, social network, in-person meetings, the analysis of structuring projects of the school unit with the theme of gender and sexuality, and through interviews with teachers and staff. The research does not propose models, pedagogies, but shifts possibilities to produce other educational logic, even within schools guided by heteronormativity through capillaries relations, micro powers, thus producing sparks subversive.